Análisis de indicadores clínicos del manejo de la teleodontología para la población adulta mayor durante la pandemia del COVID-19 en Chile. - Ly, Patricio; von Marttens, Alfredo; Ly, Andrés; Fonseca, Juan; Beltrán, Víctor (Journal of Oral Research, 2022)
Objective: To recognize the usefulness of incorporating Three-Dimensional models of standardized humans in electronic health records, in the context of the development of a teledentistry web platform designed for the attention of the elderly population in COVID-19 pandemic context. Material and Methods: A teledentistry web platform designed with different modules for clinical records. Through a new user-computer interface with a standardized virtual 3D phantom, an extraoral physical examination, an intraoral examination section was modeled. A label-associated marker is allowed to record descriptive aspects of the findings. A 3D odontogram represents multiple patient’s conditions for each of the 32 dental positions. Results: From a total of 135 patients registered on the platform, 51 markers and 33 photographs associated with the surface of the virtual 3D phantoms were recorded. For the Location parameter: Hard palate 27.6%, inserted gingiva 15.7%, tongue 15.6%. For the Type of lesion parameter (according to the information entered in the pathology selector): unidentified 35.3%, sub-prosthetic stomatitis 23.5%, irritative fibroma 9.8%. Through the registration of the exact location of the finding in the virtual phantom by a 3D marker, the 3D modeling of the oral pathologies contributed to a better diagnosis, improving the remote communication between the attending dentist and specialists. Conclusion: The combination of the 3D modeling and anatomical-referencing in a teledentistry platform can become a powerful tool for the dental practice, due to their utility and specificity.